2017
DOI: 10.24846/v26i4y201704
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evaluation of Application Layer Protocols for the Internet of Things

Abstract: Abstract:The Internet of Things is envisaged to interconnect billions of devices, from sensors and actuators to smart objects, computers and vehicles. The main obstacle that arises is that technology should allow physical objects, usually constrained devices, to interact with applications. Therefore, already existing technologies and patterns should be adapted to the new requirements, or novel ones must be created. In this context, the application layer protocols play an important part in orchestrating an IoT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The authors of [58] state that the AMQP protocol is not suitable for use in IoT systems composed of devices that are particularly limited in terms of energy. To demonstrate this, in [58], different simulations have been carried out comparing different protocols; for each protocol, a test environment has been set up and the number of bytes sent, the time needed to obtain a response and the number of packets sent have been measured. The results showed that AMQP is the protocol that sent the most data over the network with a longer send time than the other protocols.…”
Section: Amqpmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [58] state that the AMQP protocol is not suitable for use in IoT systems composed of devices that are particularly limited in terms of energy. To demonstrate this, in [58], different simulations have been carried out comparing different protocols; for each protocol, a test environment has been set up and the number of bytes sent, the time needed to obtain a response and the number of packets sent have been measured. The results showed that AMQP is the protocol that sent the most data over the network with a longer send time than the other protocols.…”
Section: Amqpmentioning
confidence: 99%
“…It must also be considered that the AMQP protocol exploits the TLS protocol to guarantee security. In conclusion, as described in [59] and [58], the use of less expensive protocols is recommended in such scenarios.…”
Section: Amqpmentioning
confidence: 99%
“…The Internet of Things is envisaged to interconnect billions of devices, from sensors and actuators to smart objects, computers and vehicles (Năstase, Sandu & Popescu, 2017). Smart mobility represents an important aspect embedded in the larger multidimensional smart city concept, characterized by personalized environments capable of providing continuous remote monitoring via sensor networks (Coardoș & Marinescu, 2020).…”
Section: Smart Mobilitymentioning
confidence: 99%
“…If they do not match, the attack will not be launched therefore no valuable data will be collected. Such elements make the data collected to be of low quality and quantity [37,38].…”
Section: Iot Honeypot Systemsmentioning
confidence: 99%